Combatting gender discrimination: A lack of fit framework. (August 2018) - Heilman, Madeline E.; Caleo, Suzette
Gender inequalities in the workplace persist, and scholars point to gender discrimination as a significant contributor. As organizations attempt to address this problem, we argue that theory can help shed light on potential solutions. This paper discusses how the lack of fit model can be used by organizations as a framework to understand the process that facilitates gender discrimination in employment decisions and to identify intervention strategies to combat it. We describe two sets of strategies. The first is aimed at reducing the perception that women are not suited for male-typed positions. The second is aimed at preventing the negative performance expectations that derive from this perception of unsuitability from influencing evaluative judgments. Also included is a discussion of several unintentional consequences that may follow from enacting these strategies. We conclude by arguing for the importance of the interplay between theory and practice in targeting gender discrimination in the workplace.